"Pengaruh Tunjangan dan Insentif terhadap Kepuasan Kerja Karyawan Kantor Desa Balung Kidul" - Nur Alifia Husna; M. Saiful Rizal; Siti Nur Kamila; Nurul Setianingrum (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the effect of allowances and incentives on employee job satisfaction at the Balung Kidul Village Office. A quantitative approach was used with a survey method and purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that incentives had a positive and significant effect on job satisfaction, while allowances had a negative effect. This indicates that employees place higher value on performance-based incentives compared to the existing allowances. The model met the classical assumptions, including normality, multicollinearity, and homoscedasticity. The study concludes that an effective compensation strategy—particularly in the form of incentives—can significantly improve job satisfaction among village government staff.